Penerapan Program Kreatif di Taman Bacaan Masyarakat Komunitas Togok di Kelurahan Ganting Kota Padang Panjang - Rahman, Fiqi Barizul; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThis article is about implementations of creative program at Togok community reading park in the city of Padang Panjang. This article aims to: (1) describe implementations of creative program at Togok community reading park in the city of Padang Panjang; (2) describe the trouble of implementations creative program at Togok community reading park in the city of Padang Panjang; and (3) describe the impact implementations of creative program at Togok community reading park in the city of Padang Panjang. The data is collected by observation, interview, and reading the literature. Based on the result of this research the conclutions are. First, the creative program that had been applied are Pondok Baca Togok, Togok Adventure Community, and Surau Adaik Togok. Second, the trouble when applied creative program are: (a) the collection of fable book is very have variation; (b) the promotion can do with the small place; and (c) less of volunteer. The impact of this implementations are: (a) children will be spontaneous to take some book that they want; (b) increase the creativity of children; and (c) increase their courage to stand in front of the public.Keywords: implementations, creative program, community reading park